Lifestyles and satisfaction with life of veteran athletes: a prospective test based on the theory of self-determination. - Batista, Marco (2021)
The practice of sports by veteran athletes is a reality with an expansion perspective. The objective was to determine predictive variables of healthy lifestyles and satisfaction with life in veteran athletes, according to the Self-determination Theory (SDT). A structural equation model and a mediation model has developed. The number of participants were 680 Portuguese veteran athletes, aged between 30 and 90 years old (M=43.78 DT=8.61). The Basic Psychological Needs Exercise Scale, the Behavioral Regulation in Sport Questionnaire, the Healthy Lifestyles Questionnaire and the Life Satisfaction Scale were used. This model has shown the following adjustments indices: ÷2 = 729.116, p < .001, ÷2/df = 4.41, CFI = .92; IFI = .92; TLI = .91; GFI = .91; RMSEA = .068; SRMR = .064. As a conclusion, in veteran athletes, the perception of satisfaction of the basic psychological needs for autonomy, leads to autonomously motivated behaviours, promoting better eating and resting habits, as well as high satisfaction with life, and a lower consumption of tobacco. Autonomous motivation has not proved to be a significant mediating variable between the basic psychological need for autonomy, lifestyles and satisfaction with life.